The Apennine brown bear: A critical review of its status and conservation problems - CIUCCI, Paolo; BOITANI, Luigi (Ursus, 2008)
The small and isolated population of brown bears (Ursus arctos marsicanus) in the Central Apennines, Italy, has been protected since the establishment of the National Park of Abruzzo, Lazio and Molise in 1923, but little active management has been implemented during the past decades to ensure effective conservation of this population. Being almost exclusively distributed within the National Park and its immediate surrounding mountains, the Apennine brown bear population suffered high human-caused mortality in the last 3 decades, but no reliable estimates of its size, trends, and vital statistics have ever been produced. Given the paucity of information available at the international level, we have critically reviewed the status of the Apennine brown bear population and have summarized data and information concerning past management. By describing the threats that appear to be the most immediate (lack of reliable knowledge, small population size, persistent illegal killing, administrative fragmentation across the bear range), we comment on what might and might not have worked in previous conservation assessments of this population. Our final aim is to substantiate more effective conservation efforts in the immediate future. The challenge of saving the Apennine brown bear calls for a renewed effort based on sound, applied research, addressing issues from basic ecology to the human dimension.